Benchmark dataset for the convex hull of 2D disks - Song, Chanyoung (Data Brief, 2019)
In this paper, we present a benchmark dataset which can be used to evaluate the algorithms to construct the convex hull of 2D disks. The dataset contains disk arrangements including general and extremely biased cases, which are generated by a C++ program. The dataset is related to an article: “QuickhullDisk: A Faster Convex Hull Algorithm for Disks” in which the QuickhullDisk algorithm is presented and compared to the incremental algorithm which was reported by Devillers and Golin in 1995 [1].